Emma Lee - Brooks, Juanita, author; Utah State University Press, publisher (Colorado State University. Libraries, 1984)
Tells the story of Emma Lee, an Englishwoman who converted to Mormonism and then became one of the nineteen wives of John D. Lee, who was convicted and executed for his role in the Mountain Meadows Massacre of September 1857.
Keywords: Mormon pioneers -- Utah -- Biography; Pioneers -- Utah -- Biography; Utah -- Biography; Lee, Emma, 1836-1897